Ultra-low Au decorated PtNi alloy nanoparticles on carbon for high-efficiency electro-oxidation of methanol and formic acid. (3rd September 2020) - Pei, An; Ruan, Luna; Liu, Bingqian; Chen, Wenqi; Lin, Shuting; Chen, Bohong; Liu, Youzhen; Zhu, Li Hua; Chen, Bing Hui
Abstract: We provide a simple method to design and prepare a highly efficient Pt10.9 Au0.2 Ni88.9 /C trimetallic nanocatalyst with a novel nanostructure of ultra-low (0.075 wt%) Au decorated PtNi alloy nanoparticles for methanol oxidation (MOR) and formic acid oxidation (FAOR). The electro-catalytic properties of Pt10.9 Au0.2 Ni88.9 /C toward the MOR and FAOR are much more excellent than Pt11.1 Ni88.9 /C, Au11.1 Ni88.9 /C and commercial Pt/C, which is attributable to the synergy effect among Pt, Au, and Ni (electron charge donor effect of Au and Ni to Pt). It has transformed the surface electronic structure of Pt atoms. Moreover, Ni triggers the rearrange towards Pt and Au atoms, it could maximize the use of noble metals. The gold atoms decorated on the surface are conducive to the formation of OHads as well as to weaken the adsorption of COads at platinum active sites. The Pt10.9 Au0.2 Ni88.9 /C catalyst also exhibits outstanding stability during the MOR and FAOR. A series of characterization techniques are adopted to reveal the nanostructures, electronic, and surficial active sites properties of Pt10.9 Au0.2 Ni88.9 /C. Graphical abstract: Image 1 Highlights: Pt10.9 Au0.2 Ni88.9 /C was obtained by chemical reduction without any surfactant. Pt10.9 Au0.2 Ni88.9 /C exhibited superior electro-catalytic activity for FAOR and MOR. Decorated Au effectively suppressed the aggregation of Ostwald ripening. Synergy effect in PtAuNi improved electro-catalytic performance in MOR and FAOR.